Self-Esteem and Relational Aggression in Students' Social Life - Fatmawati, Reza; Justitia, Dewi (Asosiasi Asesmen Pendidikan (AAP), 2025)
The phenomenon of relational aggression among students is increasingly evident in peer interactions. This condition is often associated with students’ levels of self-esteem, as individuals with lower self-esteem tend to be more vulnerable to displaying relationally aggressive behaviors. This research aims to examine the relationship between relational aggression and self-esteem among students at SMP Negeri 95 Jakarta Utara, as well as to describe the overall patterns of both variables. This research employed a descriptive quantitative approach, involving a sample of 180 students from SMP Negeri 95 Jakarta Utara. The measurement tools consisted of two questionnaires developed by the researcher. Validity testing indicated that all items in both instruments were valid, and the reliability test using Cronbach’s alpha yielded coefficients of 0.87 for the self-esteem questionnaire and 0.88 for the relational aggression questionnaire, indicating strong reliability. Data were analyzed using SPSS version 27 with a correlational technique. The findings revealed a significant relationship between self-esteem (X) and relational aggression (Y). The correlation between the two variables was categorized as weak, with a negative coefficient of –0.255, indicating that higher self-esteem is associated with lower levels of relational aggression among students.